2013
DOI: 10.1103/physrevb.88.155410
|View full text |Cite|
|
Sign up to set email alerts
|

Casimir interaction between two magnetic metals in comparison with nonmagnetic test bodies

Abstract: We present the complete results for the dynamic experiment on measuring the gradient of the Casimir force between magnetic (Ni-coated) surfaces of a plate and a sphere. Special attention is paid to the description of some details of the setup, its calibration, error analysis and background effects. Computations are performed in the framework of the Lifshitz theory at nonzero temperature with account of analytic corrections to the proximity force approximation and of surface roughness using both the Drude and t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
118
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 112 publications
(127 citation statements)
references
References 93 publications
9
118
0
Order By: Relevance
“…In spite of this, in many direct measurements of the Casimir force and its gradient performed starting in 2003 (see Refs. [4,13] for a review and more modern experiments [14][15][16][17]) the predictions of the Lifshitz theory with taken into account dissipation of free electrons were excluded at up to 99% confidence level. The predictions of the same theory with omitted dissipation of free electrons were confirmed.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In spite of this, in many direct measurements of the Casimir force and its gradient performed starting in 2003 (see Refs. [4,13] for a review and more modern experiments [14][15][16][17]) the predictions of the Lifshitz theory with taken into account dissipation of free electrons were excluded at up to 99% confidence level. The predictions of the same theory with omitted dissipation of free electrons were confirmed.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The dielectric response of metals used in computations is found from the optical data extrapolated down to zero frequency by means of the Drude model, where the relaxation parameter γ describes the energy losses of conduction electrons. It is puzzling also that if one puts γ equal to zero (as if there were no energy losses at low frequencies) the Lifshitz theory comes to good agreement with the measurement data of the same experiments [8][9][10][11][12][13][14][15][16][17] (recall that all of them have been performed at separations below 750 nm between the interacting bodies). This means that the dissipationless plasma model, which is in fact applicable only at high frequencies in the region of infrared optics, works well for some reasons even at low frequencies characteristic of the normal skin effect.…”
Section: Introductionmentioning
confidence: 99%
“…On the background of Casimir forces, one could also search for axions and other axion-like particles [13][14][15][16][17][18][19][20] which are considered as hypothetical constituents of dark matter. It is remarkable that taken together, dark energy and dark matter contribute for more than 95% of the energy of the Universe, leaving less than 5% to the forms of energy we are presently capable to observe directly [6].Precise measurements of the Casimir force revealed a problem that the experimental data agree with theoretical predictions of the fundamental Lifshitz theory only under the condition that in calculations one disregards the relaxation properties of conduction electrons and the conductivity at a constant current for metallic and dielectric boundary surfaces, respectively (see review in [5,21] and more modern experiments [22][23][24][25][26][27]). Theoretically, it was shown that an inclusion of the relaxation properties of conduction electrons and the conductivity at a constant current in computations results in a violation of the Nernst heat theorem for the Casimir entropy (see review in [5,21] and further results [28][29][30][31]).…”
mentioning
confidence: 99%